Bilderwelten : ägyptische Bilder und ägyptologische Kunst : Vorarbeiten für eine bildwissenschaftliche Ägyptologie - Widmaier, Kai. (Probleme der Ägyptologie, 2017)
Egyptologists have been debating for decades about whether or not Egyptian images classify as art . Nevertheless, the term 'art' still serves as a guiding concept for Egyptology. Kai Widmaier offers an overview of how different art-historical interpretive methods influence Egyptological research. His study demonstrates that, due to its adherence to the term art , Egyptology has considerably dissociated Egyptian images from their original contexts. Bilderwelten combines the analysis of Egyptian images from the 6th to the 18th Dynasty with methodological reflection. This leads to both a new terminology of style as well as to an alternative approach to Egyptian images. By differentiating systematically between Egyptian images and Egyptological art , this book lays the foundation for an Egyptology that follows the path of Visual Studies instead of adhering to questionable art-historical methods.